Combination valve remanufacturing method based on laser combined machining technology

The combined valve of the water injection pump is remanufactured through laser composite processing technology to form a high-strength alloy layer, which solves the failure problem of the combined valve due to corrosion, improves the performance and service life of the combined valve, and realizes an environmentally friendly remanufacturing process.

CN119465137APending Publication Date: 2025-02-18SHAANXI YANCHANG PETROLEUM GRP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411658927.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

During long-term use, the water injection pump combination valve fails due to high-pressure water erosion and impurity corrosion. The traditional repair methods have problems such as low accuracy, large waste of materials and serious environmental pollution.

Method used

Remanufacturing methods based on laser composite processing technology, including combined valve pre-treatment, infrared scanning three-dimensional modeling, laser melt deposition and laser alloying treatment, are used to form a high-intensity alloy layer to improve the performance and service life of the combined valve.

Benefits of technology

Through laser composite processing technology, the alloy layer formed has high hardness, high self-corrosion potential and low corrosion current density, which effectively delays wear and corrosion in vulnerable parts, improves the service life of the combined valve, and reduces environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119465137A_ABST
    Figure CN119465137A_ABST
Patent Text Reader

Abstract

The invention discloses a combination valve remanufacturing method based on a laser combined machining technology. The combination valve remanufacturing method comprises the following steps that the damage degree and remanufacturing performance are determined, turning is conducted, and sand blasting is conducted; carrying out three-dimensional scanning on the model by using an infrared scanner to obtain a size, modeling, and carrying out hierarchical processing on the model; the pre-treated combination valve is subjected to laser melting deposition along the surface of the combination valve until the size of the combination valve is 0.3-0.6 mm larger than the design size of the model, and machining is conducted; and coating the surface of the mechanically processed combination valve with an alloyed organic coating, drying, and carrying out laser alloying treatment on the combination valve by adopting a conductor optical fiber coupling laser. Wherein the alloyed organic coating is prepared from a 5% polyvinyl alcohol solvent and mixed powder, every 100 ml of the alloyed organic coating contains 25-30 g of the mixed powder, and the mixed powder is formed by mixing Ti powder, Si powder and B4C powder according to the mass ratio of 60: 14: 1. The corrosion resistance of the remanufactured combination valve is improved by 64% or above compared with that of a 2Cr13 base material, and the erosion service life is prolonged by 4 times or above.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of mechanical manufacturing, and in particular relates to a highly efficient and environmentally friendly remanufacturing method for a water injection pump combination valve based on a laser composite processing technology. Background Art

[0002] The combination valve of water injection pump is an important fluid control equipment in the fields of petrochemical industry, water treatment, etc. The stability and reliability of its performance directly affect the operating efficiency of the whole system. However, in actual use, due to the continuous flushing of high-pressure water (20-40MPa) and impurities in the water during long-term use, the combination valve is severely eroded. This failure causes the pressure and efficiency of the water injection pump to decrease, seriously affecting the operation of the water pump. In this way, the combination valve needs to be repaired or replaced. Traditional repair methods often use mechanical processing or welding, which have problems such as low processing accuracy, large material waste, and serious environmental pollution. Therefore, developing an efficient and environmentally friendly remanufacturing method is of great significance to improving the service life and performance of the combination valve. Summary of the invention

[0003] The purpose of the present invention is to provide a combination valve remanufacturing method based on laser composite processing technology, by remanufacturing the waste combination valve, the waste combination valve can be reused, the cost can be reduced, and the performance and service life of the remanufactured combination valve can be improved.

[0004] A combined valve remanufacturing method based on laser composite processing technology comprises the following steps: (1) Pre-treatment of combination valve: determine the degree of damage and remanufacturing, turning, sand blasting; (2) Combination valve model processing: Use an infrared scanner to perform three-dimensional scanning on the pre-processed combination valve, obtain the size, build the model, and perform layer processing on the model with a layer thickness of 0.3 to 0.4 mm; (3) Laser melting forming: The pre-treated combined valve is laser melted and deposited along its surface to a size 0.3 to 0.6 mm larger than the model design size, and then machined; (4) Laser alloying treatment: brushing the alloyed organic coating on the surface of the combination valve after mechanical processing in step (3), drying, and performing laser alloying treatment on the combination valve using a conductor fiber coupled laser; The alloyed organic coating in step (4) is prepared by mixing 5% polyvinyl alcohol solvent and mixed powder. Each 100 ml of the organic solvent contains 25 g to 30 g of mixed powder. The mixed powder is a mixture of Ti powder, Si powder and B4C powder in a mass ratio of 60:14:1.

[0005] Preferably, the material used for the laser melting deposition in step (3) is alloy powder, and the alloy powder is spherical powder with a particle size of 53 to 150 μm and a purity of 99.95%.

[0006] Preferably, the alloy powder comprises the following components based on mass percentage of 100%: C: ≤0.25, Mn: ≤2.00, Si: ≤1.50, Cr: 24.0-26.0, Ni: 19.0-21.0, Mo: 1.50-2.50, P: ≤0.035, S: ≤0.03, and the balance is Fe.

[0007] Preferably, the size of the coating in step (4) is 240 to 300 μm.

[0008] Preferably, the mixed powder is spherical and has a particle size of 80 to 110 nm.

[0009] Preferably, the surface roughness of the machining in step (3) needs to be controlled to be less than Ra3.2 μm.

[0010] Preferably, the laser melting deposition process in step (3) is as follows: laser power is 1450-1750 W, scanning speed is 400-600 mm / min, overlap rate is 40%-60%, laser beam is a circular spot, and spot diameter is about 3 mm.

[0011] Preferably, the drying in step (4) is a step-by-step temperature drying, specifically: controlling the heating rate to ≤5°C / min, heating to 120°C and keeping warm for 2h.

[0012] Preferably, the process of laser alloying treatment in step (4) is: spot diameter 3 mm, laser power 900-1000 W, scanning speed 1500 mm / min, overlap rate 30% to 40%.

[0013] Beneficial effects of the present invention: 1) The alloy layer formed by the laser melting deposition and laser alloying combined technology is metallurgically bonded to the base material, with high bonding strength, which can effectively prevent the surface alloy layer from falling off and cracking. The alloy layer has the characteristics of high hardness, high self-corrosion potential, and low corrosion current density, which can effectively delay the wear and corrosion of vulnerable parts and effectively improve the service life of the combination valve; at the same time, the combination valve remanufacturing method is green and environmentally friendly, which can effectively reduce environmental pollutants in the remanufacturing process; 2) The corrosion resistance of the remanufactured combination valve of the present invention is improved by more than 64% compared with the 2Cr13 substrate, and the erosion life is increased by more than 4 times. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 This is the microstructure of the laser melt deposited layer in Example 1.

[0015] Figure 2 This is the microstructure of the laser melt deposited layer in Example 2.

[0016] Figure 3 This is the microstructure of the laser melt deposited layer in Example 3. DETAILED DESCRIPTION

[0017] Example 1 The combined valve of a water injection pump in an oil field failed after 13 days of use. Its material grade was 2Cr13. (1) Pre-treatment of the surface of the waste combination valve: clean the waste combination valve with petroleum ether to remove rust, then use penetrant testing and ultrasonic testing to detect the damaged parts to determine the degree of damage and remanufacturing ability; for the remanufactured waste combination valve, remove the surface cracks and fatigue layer through mechanical turning, and finally perform sandblasting on the surface; (2) Remanufacturing model building: Use an infrared scanner to perform a three-dimensional scan on the pre-processed combination valve to obtain the dimensions of the waste combination valve. Based on the above data, the remanufacturing processing model is designed and the remanufacturing model is layered with a layer thickness of 0.3 mm. (3) Laser melting forming remanufacturing processing: The pre-treated waste combination valve is subjected to laser melting deposition along its surface using a fiber laser processing system; the laser processing process parameters are as follows: laser power is 1450W, scanning speed is 600mm / min, overlap rate is 60.0%, laser beam is a circular spot, spot diameter is 3mm, and layer by layer melting and deposition is performed until it is 0.3mm larger than the model design size. The material used for laser melting deposition of the combination valve is alloy powder, and the specific composition is calculated based on the mass percentage of 100%, C: ≤0.25, Mn: ≤2.00, Si: ≤1.50, Cr: 24.0~26.0, Ni: 19.0~21.0, Mo: 1.50~2.50, P: ≤0.035, S: ≤0.03, and the remainder is Fe. The material is spherical powder with a particle size between 53-150 microns and a purity of 99.95%; the structure after laser melting forming is shown in Figure 1 After the laser melting deposition is completed, the formed combination valve is machined to control the surface roughness below Ra3.2μm; (4) Using laser alloying treatment, an alloyed organic coating is prepared with 5% polyvinyl alcohol solvent and mixed powder. Each 100 ml of the organic solvent contains 30 g of mixed powder. The mixed powder is a mixture of Ti powder, Si powder and B4C powder in a mass ratio of 60:14:1. The mixed powder particles are spherical and have a particle size between 80 and 100 nm. The organic coating is evenly applied to the surface of the combination valve with a brush. The thickness of the preset alloying material can be controlled between 260 and 280 μm. After the organic coating is applied to the surface of the combination valve, the workpiece is dried by a step-by-step heating method. The heating rate can be controlled to be ≤5°C / min during the heating stage, and the temperature is kept at 120°C for 2 hours. Finally, a semiconductor fiber-coupled laser is used to alloy the combination valve. The specific process is: spot diameter: 3 mm, laser power 1000 W, scanning speed 1500 mm / min, overlap rate 30%;

[0018] Performance testing: The quality of the remanufactured combination valve was inspected, and the inspection results are as follows: the dimensional accuracy and roughness of each part meet the requirements, and the roughness is Ra1.79μm; the hardness of the remanufactured part was tested with a Vickers microhardness tester, and the test conditions were: load 5N, loading time 10s, and holding time 10s. The test results showed that the average hardness of the laser melt deposition layer was HV652.3, and the average hardness of the laser alloying layer was HV1463.7; the polarization curve was tested using an electrochemical workstation, and the test conditions were: scanning potential range -1000mV~1000mV, scanning speed 0.5mV / s, the corrosion medium was the on-site injection water of an oil field, the experimental temperature was 35℃, and the test results showed that the self-corrosion potential of 2Cr13 steel was -321.8mV, the corrosion current density of 2Cr13 steel was 1.74μA / cm, the self-corrosion potential of the remanufactured alloy layer was -173.1mV, and the corrosion current density of the remanufactured alloy layer was 0.62μA / cm; the erosion corrosion resistance was tested using an erosion corrosion tester. The test conditions were: temperature 25°C, rotation speed 12m / s, test cycle 48h, and the test medium was the oil field on-site injection water (containing 1% sand and gravel). The test results were 1.6127mm / a for 2Cr13 steel and 0.3823mm / a for the remanufactured alloy layer. After remanufacturing, the combination valve was installed and used on the original water injection pump of the oil field, with a service life of 93 days.

[0019] Example 2 The combined valve of a water injection pump in an oil field failed after 15 days of on-site use. Its material grade was 0Cr17Ni4Cu4Nb. (1) Pre-treatment of the surface of the waste combination valve: clean the waste combination valve with petroleum ether to remove rust, then use penetrant testing and ultrasonic testing to detect the damaged parts to determine the degree of damage and remanufacturing ability; for the remanufactured waste combination valve, remove the surface cracks and fatigue layer through mechanical turning, and finally perform sandblasting on the surface; (2) Remanufacturing model building: Use an infrared scanner to perform a three-dimensional scan on the pre-processed combination valve to obtain the dimensions of the waste combination valve. Based on the above data, the remanufacturing processing model is designed and the remanufacturing model is layered with a layer thickness of 0.5 mm. (3) Laser melting forming remanufacturing processing: The pre-treated waste combination valve is subjected to laser melting deposition along its surface using a fiber laser processing system; the laser processing process parameters are as follows: laser power is 1600W, scanning speed is 600mm / min, overlap rate is 60.0%, laser beam is a circular spot, spot diameter is 3mm, and layer by layer melting and deposition is performed until it is 0.6mm larger than the model design size. The material used for laser melting deposition of the combination valve is alloy powder, and the specific composition is calculated by mass percentage as follows: C: ≤0.25, Mn: ≤2.00, Si: ≤1.50, Cr: 24.0~26.0, Ni: 19.0~21.0, Mo: 1.50~2.50, P: ≤0.035, S: ≤0.03, and the remainder is Fe. The material is spherical powder with a particle size between 53 and 150 microns and a purity of 99.95%; the structure after laser melting forming is shown in Figure 1. Figure 2 After the laser melting deposition is completed, the formed combination valve is machined to control the surface roughness below Ra3.2μm; (4) Using laser alloying treatment, an alloyed organic coating is prepared with 5% polyvinyl alcohol solvent and mixed powder. Each 100 ml of the organic solvent contains 26 g of mixed powder. The mixed powder is a mixture of Ti powder, Si powder and B4C powder in a mass ratio of 60:14:1. The mixed powder particles are spherical and have a particle size between 80 and 100 nm. The organic coating is evenly applied to the surface of the combination valve with a brush. The thickness of the preset alloying material can be controlled between 250 and 300 μm. After the organic coating is applied to the surface of the combination valve, the workpiece is dried by a step-by-step heating method. The heating rate can be controlled to be ≤5°C / min during the heating stage, and the temperature is kept at 120°C for 2 hours. Finally, a semiconductor fiber-coupled laser is used to alloy the combination valve. The specific process is: spot diameter: 3 mm, laser power 950 W, scanning speed 1500 mm / min, overlap rate 35%;

[0020] Performance test: The remanufactured combination valve was quality tested, and the test results are as follows: the dimensional accuracy and roughness of each part meet the requirements, and the roughness is Ra0.62μm; the hardness of the remanufactured part was tested using a Vickers microhardness tester, and the test conditions were: load 5N, loading time 10s, and holding time 10s. The test results showed that the average hardness of the laser melt deposition layer was HV649.5, and the average hardness of the laser alloying layer was HV1503.4; the polarization curve was tested using an electrochemical workstation, and the test conditions were: scanning potential range -1000mV~1000mV, scanning speed 0.5mV / s, the corrosive medium was water injected on site in an oil field, the experimental temperature was 35℃, and the test results showed that the self-corrosion potential of 0Cr17Ni4Cu4Nb steel was -261.7mV, and the corrosion current density of 0Cr17Ni4Cu4Nb steel was 1.42μA / cm, the self-corrosion potential of the remanufactured alloy layer is -155.1mV, and the corrosion current density of the remanufactured alloy layer is 0.62μA / cm; the erosion corrosion resistance is tested using an erosion corrosion tester, and the test conditions are: temperature 25℃, speed 12m / s, test cycle 48h, and the test medium is the oil field on-site injection water (containing 1% sand and stone). The test results are 0Cr17Ni4Cu4Nb steel 1.7362mm / a, and the remanufactured alloy layer 0.3747mm / a. After remanufacturing, the combination valve was installed and used on the original water injection pump of the oil field, and its service life is 109 days.

[0021] Example 3 The combined valve of a water injection pump in an oil field failed after 18 days of on-site use. Its material grade was 2Cr13. (1) Pre-treatment of the surface of the waste combination valve: clean the waste combination valve with petroleum ether to remove rust, then use penetrant testing and ultrasonic testing to detect the damaged parts to determine the degree of damage and remanufacturing ability; for the remanufactured waste combination valve, remove the surface cracks and fatigue layer through mechanical turning, and finally perform sandblasting on the surface; (2) Remanufacturing model building: Use an infrared scanner to perform a three-dimensional scan on the pre-processed combination valve to obtain the dimensions of the waste combination valve. Based on the above data, the remanufacturing processing model is designed and the remanufacturing model is layered with a layer thickness of 0.4 mm. (3) Laser melting forming remanufacturing processing: The pre-treated waste combination valve is subjected to laser melting deposition along its surface using a fiber laser processing system; the laser processing process parameters are as follows: laser power is 1750W, scanning speed is 400mm / min, overlap rate is 40.0%, laser beam is a circular spot, spot diameter is 3mm, and layer by layer melting and deposition is performed until it is 0.5mm larger than the model design size. The material used for laser melting deposition of the combination valve is alloy powder, and the specific composition is calculated based on the mass percentage of 100%, C: ≤0.25, Mn: ≤2.00, Si: ≤1.50, Cr: 24.0~26.0, Ni: 19.0~21.0, Mo: 1.50~2.50, P: ≤0.035, S: ≤0.03, and the remainder is Fe. The material is spherical powder with a particle size between 53-150 microns and a purity of 99.95%; the structure after laser melting forming is shown in Figure 3 After the laser melting deposition is completed, the formed combination valve is machined to control the surface roughness below Ra3.2μm; (4) Using laser alloying treatment, an alloyed organic coating is prepared with 5% polyvinyl alcohol solvent and mixed powder. Each 100 ml of the organic solvent contains 28 g of mixed powder. The mixed powder is a mixture of Ti powder, Si powder and B4C powder in a mass ratio of 60:14:1. The mixed powder particles are spherical and have a particle size between 90 and 110 nm. The organic coating is evenly applied to the surface of the combination valve with a brush. The thickness of the preset alloying material can be controlled between 280 and 300 μm. After the organic coating is applied to the surface of the combination valve, the workpiece is dried by a step-by-step heating method. The heating rate can be controlled to be ≤5°C / min during the heating stage, and the temperature is kept at 120°C for 2 hours. Finally, a semiconductor fiber-coupled laser is used to alloy the combination valve. The specific process is: spot diameter: 3 mm, laser power 900 W, scanning speed 1500 mm / min, overlap rate 40%;

[0022] Performance testing: The quality inspection of the remanufactured combination valve is carried out, and the inspection results are as follows: the dimensional accuracy and roughness of each part meet the requirements, and the roughness is Ra0.55μm; the hardness of the remanufactured part is tested by a Vickers microhardness tester, and the test conditions are: load 5N, loading time 10s, and holding time 10s. The test results show that the average hardness of the laser melt deposition layer is HV672.3, and the average hardness of the laser alloying layer is HV1481.6; the polarization curve is tested by an electrochemical workstation, and the test conditions are: scanning potential range -1000mV~1000mV, scanning speed 0.5mV / s, the corrosion medium is the injection water of an oil field, the experimental temperature is 35℃, and the test results show that the self-corrosion potential of 2Cr13 steel is -253.4mV, the corrosion current density of 2Cr13 steel is 1.51μA / cm, the self-corrosion potential of the remanufactured alloy layer is -141.7mV, and the corrosion current density of the remanufactured alloy layer is 0.59μA / cm; the erosion corrosion resistance was tested using an erosion corrosion tester. The test conditions were: temperature 25°C, rotation speed 12m / s, test cycle 48h, and the test medium was the oil field on-site injection water (containing 1% sand and gravel). The test results were 1.682mm / a for 2Cr13 steel and 0.3566 mm / a for the remanufactured alloy layer. After remanufacturing, the combination valve was installed and used on the original injection pump of the oil field, with a service life of 97 days.

Claims

1. A combined valve remanufacturing method based on laser composite processing technology, characterized in that: The following steps are involved: (1) Pre-treatment of combination valve: determine the degree of damage and remanufacturing, turning, sand blasting; (2) Combination valve model processing: Use an infrared scanner to perform three-dimensional scanning on the pre-processed combination valve, obtain the size, build the model, and perform layer processing on the model with a layer thickness of 0.3 to 0.4 mm; (3) Laser melting forming: The pre-treated combined valve is laser melted and deposited along its surface to a size 0.3 to 0.6 mm larger than the model design size, and then machined; (4) Laser alloying treatment: brushing the alloyed organic coating on the surface of the combination valve after mechanical processing in step (3), drying, and performing laser alloying treatment on the combination valve using a conductor fiber coupled laser; The alloyed organic coating in step (4) is prepared by mixing 5% polyvinyl alcohol solvent and mixed powder. Each 100 ml of the organic solvent contains 25 g to 30 g of mixed powder. The mixed powder is a mixture of Ti powder, Si powder and B4C powder in a mass ratio of 60:14:

1.

2. The combined valve remanufacturing method based on laser composite processing technology according to claim 1 is characterized in that: The material used for the laser melting deposition in step (3) is alloy powder, which is spherical powder with a particle size of 53 to 150 μm and a purity of 99.95%.

3. The combined valve remanufacturing method based on laser composite processing technology according to claim 2 is characterized in that: The alloy powder comprises the following components based on mass percentage of 100%: C: ≤0.25, Mn: ≤2.00, Si: ≤1.50, Cr: 24.0-26.0, Ni: 19.0-21.0, Mo: 1.50-2.50, P: ≤0.035, S: ≤0.03, and the balance is Fe.

4. The combined valve remanufacturing method based on laser composite processing technology according to claim 1 is characterized in that: The size of the coating in step (4) is 240 to 300 μm.

5. The combined valve remanufacturing method based on laser composite processing technology according to claim 1 is characterized in that: The mixed powder is spherical and has a particle size of 80 to 110 nm.

6. The combined valve remanufacturing method based on laser composite processing technology according to claim 1 is characterized in that: The surface roughness of the machining process in step (3) needs to be controlled to be less than Ra3.2μm.

7. The combined valve remanufacturing method based on laser composite processing technology according to claim 1 is characterized in that: The laser melting deposition process in step (3) is as follows: laser power 1450-1750 W, scanning speed 400-600 mm / min, overlap rate 40%-60%, laser beam is a circular spot, and the spot diameter is about 3 mm.

8. The combined valve remanufacturing method based on laser composite processing technology according to claim 1 is characterized in that: The drying in step (4) is a step-by-step heating method, specifically: controlling the heating rate to ≤5°C / min, heating to 120°C and keeping the temperature for 2h.

9. The combined valve remanufacturing method based on laser composite processing technology according to claim 1 is characterized in that: The process of laser alloying treatment in step (4) is: spot diameter 3mm, laser power 900-1000W, scanning speed 1500mm / min, overlap rate 30%-40%.

10. The combined valve remanufacturing method based on laser composite processing technology according to claim 1, characterized in that: The specific process for determining the degree of damage and remanufacturing in step (1) is as follows: first, cleaning and rust removal are performed using petroleum ether, and then penetrant testing and ultrasonic testing are used to determine the degree of damage and remanufacturing.